2016
DOI: 10.1097/ceh.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-Based Study of Factors Explaining General Practitioners' Intention to Use and Participation in Electronic Continuing Medical Education

Abstract: Perceived behavioral control and attitude constitute the main predictors of the intention to use eCME. Establishing discussions forums and strengthening organizational support for eCME through an increased awareness among clinical superiors and CME managers would be expected to increase GPs' intention to use eCME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Among the three constructs, perceived behavioral control and attitudes had higher effects, followed by subjective norms. Our result is similar to prior research which implied that e-learning usage intention is dependent on individual behavior control [ 23 , 28 ]. Another study reported that medical students’ behavioral control was a determining factor in their intention to continue receiving m-learning [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Among the three constructs, perceived behavioral control and attitudes had higher effects, followed by subjective norms. Our result is similar to prior research which implied that e-learning usage intention is dependent on individual behavior control [ 23 , 28 ]. Another study reported that medical students’ behavioral control was a determining factor in their intention to continue receiving m-learning [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The quantitative approach has been widely used in previous technology research [ 26 , 28–30 ]. For such studies, the questionnaires are considered the most reliable tool to measure relationships among constructs in the research model [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intention is determined by three variables: 1) attitudes (overall evaluation of the behaviour), 2) subjective norms (estimation of the social pressure to carry out the behaviour), and 3) perceived behavioural control (the extent to which a person feels able to perform the behaviour). Given the challenges of measuring actual behaviour, intention can be used as a proxy, where a positive relationship between intention and behaviour has been confirmed [14]. This assumption has been supported for behaviours among clinicians [5].…”
Section: Introductionmentioning
confidence: 86%